Princess [large type] - Patterson, James, 1947-; Jones, Rees, 1983- (Patterson, James, 1947- Private novels., 2018)
When Princess Caroline, third in line to the British throne, hires Jack Morgan to find a close friend before the media finds out, he knows the princess is hiding something.